Desarrollo de un sistema de comunicación remota vía modem con un pc que se encuentra apagado - Mosquera Palacios, Darin Jairo; Salcedo Parra, Octavio; Patiño Bernal, Marlon (Revista Científica, 2007)
This article is a partial result of the research project "Sistema de Gestión en Línea de un Pc por Internet" where two computers communicate themselves on Internet, and overcomes one of the obstacles that comes up when one of the equipments is physically distant and turned off. Willing to facilitate information interchange, this work aims to wipe out this hindrance by avoiding worming about the remote equipment, but about the kind or information and/or the software set up required.